INTERVENÇÃO EDUCATIVA COM PROFISSIONAIS DA ATENÇÃO PRIMÁRIA À SAÚDE SOBRE DIREITOS DE MULHERES E CRIANÇAS: Repercussões no cuidado em saúde durante os primeiros mil dias - SOUSA, Francenilde Silva de (2025)
Objective. To evaluate the effect of an educational intervention on the rights of women and children on the work processes of Primary Health Care (PHC) professionals, especially Community Health Agents (CHAs), and on health indicators during the first thousand days. Materials and Methods. This was a qualitative and quantitative study carried out in Alcântara, a small municipality in Maranhão with a low Municipal Human Development Index and predominantly rural and quilombola communities. A municipality in the same health region with similar characteristics was chosen as the control. The intervention consisted of three stages: the exploratory phase, the educational action and the evaluation. The first served to organize the field. The second stage consisted of an 8-month training course (April to December of 2022) on women's and children's rights in the first 1000 days. The third stage was an evaluation with two approaches. In the quantitative approach, a non-randomized community trial was carried out whose units of analysis were Alcântara (intervention municipality) and Guimarães (control), and the outcomes were ten indicators related to women and children in the first 1,000 days of life, collected from the Health Information System for PHC. Descriptive analyses, Prais-Winsten linear regression and interrupted time series controlled using autoregressive, integrated and moving average models were carried out. The qualitative, action research, with data collected through collective interviews, included all the CHAs who took part in the intervention. The interviews were recorded, transcribed and analyzed using thematic content analysis. All ethical aspects were respected in both approaches (approval by the HUUFMA, on 12/12/2018, CAAE No. 92281818.9.1001.5086). Results. Manuscript 1 (to be submitted to The Lancet Regional Health - Americas). When analyzing the time trend of six women's and four children's health indicators, we found that, twelve months after the end of the intervention in Alcântara, there was a significant increase in the number of consultations for follow-up of pregnant women (regression coefficientβ=64.92; 95%CI: 34.33 to 95.51), in the number of children breastfed up to the age of two (β=10.62; 95%CI: 5.01 to 16.23) and in the number of children with up-to-date vaccinations (β=3 0.33; 95%CI: 8.61 to 52.04), but there was a reduction in the number of coletive educational actions aimed at pregnant women (β= -3.25; 95%CI: -5.94 to -0.56). In Guimarães, all the indicators showed negative coefficients, indicating a reduction in actions during the period studied. Manuscript 2 (to be submitted to Plos One). In this qualitative study, the professionals' perceptions of the effectiveness of the intervention were grouped into three categories of analysis: i) The intervention as a tool for empowering CHAs; ii) The intervention as a strategy for changing CHAs' working practices; and iii) The methodological paths and the value of the intervention. The CHAs reported greater autonomy and security to discuss rights with the users; changes in the frequency of visits to the communities and in the work strategy; and consolidation of ties with the community. The intervention was evaluated very positively, but some challenges were the displacement of professionals for the course and work activities, as well as aspects outside their control that could improve the results, such as teamwork, infrastructure and others. Manuscript 3 (accepted for publication in the journal PBOCI). In this study, entitled Perception of Family Health Strategy workers on oral health care provided to women and children in the first 1,000 days, a qualitative methodology was used and two categories emerged: i) Dental care for pregnant women and children in the first 1,000 days of life: contradictions between thinking (myths/beliefs) and doing; ii) Oral health education in the first 1,000 days of life.In the first, the professionals mentioned barriers to accessing dental care due to myths about the possibility of treatment, which were not restricted to users' knowledge, but included that of health professionals.In the second, the participants mentioned health education problems in which the community does not listen to or understand the professionals. Thus, we identified that there is a gap in the continuing education of professionals in relation to oral health in the first 1,000 days of life, especially with regard to dental care during pregnancy. Professionals are still unable to make the population recognize dental care as a right to health. Final considerations: The educational intervention contributed to improving maternal and child health care during the first thousand days of life, strengthening the idea that well-planned educational strategies, aligned with local realities and PHC principles, are potential tools for transforming professional practices and empowering communities to seek their rights. The effects of the intervention on women's and children's health indicators persisted even 12 months after the end of the actions. However, the intervention did not have an impact on several crucial aspects in the 1000 days, such as exclusive breastfeeding, consultations and exams, which are outside the control of the CHAs. We recommend implementing this educational action in the permanent training plan for PHC professionals, with an emphasis on CHAs.